(untitled) (Eurasian Medical Research Periodical, 2026)
The widespread use of high-dose melphalan in conditioning regimens for allogeneic hematopoietic stem cell transplantation (allo-HSCT) has led to an increased incidence of melphalan-associated enteropathy (MAE), a severe toxic intestinal injury. A key challenge in management is its differentiation from acute graft-versus-host disease (GVHD)